Sodium-rich polyanion positive electrode material and preparation method thereof
By adjusting the chemical composition of the positive electrode material of sodium ion battery, increasing the sodium content, controlling the solution pH value and chelating transition metal ions, the problems of high Na+ diffusion energy barrier and low electron conductivity caused by the distortion of the unit cell in the existing materials are solved. The material has excellent rate performance, good cycle stability and high capacity.
Patent Information
- Application Number
- CN202411730904.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing sodium ion battery positive electrode material Na3MnTi(PO4)3 is a unit cell structure distorted due to the Jahn-Teller effect of Mn and the difference in ion radius of Mn and Ti, resulting in high Na+ diffusion energy barrier and low electron conductivity, limiting the material's magnification. Performance, cycle stability and capacity exertion.
By adjusting the chemical composition of the material, a sodium-rich polyanionic positive electrode material with the general structure formula of NazMnTi1-x-yMxAy(PO4)3 was prepared, and the sodium content was increased to fill the sodium vacancy in the material, and the solution pH value was controlled by organic acids and Chelate transition metal ions to ensure the pure phase degree and electron conductivity of the material.
The material has excellent rate performance, good cycle stability and high capacity performance. It still has a capacity of about 150mAh/g at a rate of 10 C, and the capacity retention rate of 100 cycles exceeds 95%.
Smart Images

Figure CN119481011A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium ion batteries, and in particular to a sodium-rich polyanion positive electrode material. Background Art
[0002] Among the many energy storage technologies currently available, electrochemical energy storage has the characteristics of high energy density, fast charge and discharge response speed, high conversion efficiency, and no geographical restrictions. Among them, lithium-ion batteries are one of the most widely used technologies for electrochemical energy storage, with high operating voltage, high energy density, long cycle times, easy modularization, and obvious advantages. As lithium-ion batteries become more and more mature, the demand is also increasing.
[0003] Since the price of battery-grade lithium carbonate has been rising since 2022, it has been difficult to achieve large-scale energy storage relying solely on lithium-ion batteries. Sodium-ion batteries have a similar working principle to lithium-ion batteries, and sodium is abundant in the earth's crust, widely distributed, and has lower costs. They have the potential to replace lithium-ion batteries and become the mainstream technology for large-scale energy storage.
[0004] Phosphate materials are one of the polyanion cathode materials for sodium ion batteries. They have the following advantages: adjustable operating voltage; a wide variety of synthetic elements, abundant resources, and low cost; a relatively stable structure, which is Na + Provide stable space for storage.
[0005] Na3MnTi(PO4)3 has a stable three-dimensional framework structure and a sufficiently high theoretical specific capacity (176 mAh g -1 ), which can achieve three-electron reaction and high redox potential (Mn 2+ / Mn 3+ , 3.6 V; Mn 3+ / Mn 4+ , 4.0 V). The elements of this material have the advantages of high abundance and low cost, and have great application potential. However, this material is limited by the Jahn-Teller effect of Mn and the large difference in ion radius between Mn and Ti, which causes the distortion of the unit cell structure and leads to Na + Problems such as high diffusion energy barrier and low electronic conductivity of materials hinder the further development and application of materials. Summary of the invention
[0006] The present invention aims to provide a sodium-rich polyanion positive electrode material and a preparation method thereof, which has the characteristics of excellent rate performance, cycle stability and high gram capacity.
[0007] The present invention can be implemented by the following technical solutions: The present invention discloses a sodium-rich polyanion positive electrode material, the general structural formula of which is Na z MnTi 1-x- y M x A y (PO4)3 (space group (R-3c)); the value range of z is 3<z≤4, the value range of x is 0<x<1, and the value range of y is 0<y≤0.33; M is one or more of the metal elements Al, V, Cr, Mn, Fe, Ni, Cu, and Zn, and A is one or more of the alkali metal or alkaline earth metal elements Li, Na, K, Mg, and Ca.
[0008] Another aspect of the present invention is to protect the preparation method of the above-mentioned sodium-rich polyanion positive electrode material, comprising the following steps: S1. Preparation of a first precursor solution: dissolving a manganese source, a titanium source, a metal M source, an alkali metal or alkaline earth metal A source, a carbon source and a first acid solution to form a first precursor solution, and adding a second acid solution organic acid to control the pH value of the first precursor solution to be in the range of 1 to 3; S2, preparation of a second precursor solution: mixing and dissolving a sodium source and a phosphorus source to form a second precursor solution; S3, preparation of a third precursor solution: uniformly mixing the second precursor solution with the first precursor solution to obtain a third precursor mixed system; S4, preparation of precursor powder: drying the third precursor mixture system to obtain precursor powder; S5. Sintering preparation of sodium-rich polyanion positive electrode material: The precursor powder is calcined at high temperature and then cooled to obtain the sodium-rich polyanion positive electrode material.
[0009] Furthermore, in step S1, the feed ratio of the manganese source, the titanium source, the metal M source, and the A source is prepared according to a metal ion molar ratio of 1: (0.01-0.99): (0.01-0.99): (0.01-0.33).
[0010] Furthermore, in step S2, the feeding ratio of the sodium source and the phosphorus source is prepared according to a sodium-phosphorus molar ratio of 1 to 1.5.
[0011] Furthermore, in step S3, the first precursor solution and the second precursor solution are fed in a ratio according to a molar ratio of phosphorus to manganese of 0.5-5.
[0012] Furthermore, in step S4, the drying method is flash drying and / or spray drying, and the drying temperature ranges from 110 to 250°C.
[0013] Furthermore, in step S5, the high temperature calcination conditions are: sintering temperature is 550-750°C, holding time is 5-15h, and calcination atmosphere is an inert atmosphere, which is argon and / or nitrogen.
[0014] Furthermore, in steps S1 and S2, the manganese source is one or more of manganese sulfate, manganese acetate, manganese chloride, and manganese nitrate; the titanium source is one or more of titanium tetrachloride, tetrabutyl titanate, isopropyl titanate, titanium isopropoxide, titanium sulfate, titanyl sulfate, bis(trifluoromethanesulfonate) titanocene, and dihydroxybis(ammonium lactate) titanium; the metal M source is one or more of the sulfate, chloride, nitrate, and oxalate of M; the alkali metal or alkaline earth metal A source is one or more of the sulfate, chloride, nitrate, carbonate, and oxalate of A.
[0015] Furthermore, in step S1, the carbon source is one or more of glucose, citric acid, sucrose, maltose, water-soluble starch, and lactose, and the added amount of the carbon source is 0.5~10wt%; the first acid solution is one or more of nitric acid, acetic acid, formic acid, oxalic acid, ascorbic acid, tartaric acid, and citric acid.
[0016] Furthermore, in step S2, the sodium source is one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium formate, sodium acetate, sodium sulfate, sodium nitrate, and trisodium citrate; the phosphorus source is one or more of phosphoric acid, sodium monohydrogen phosphate, sodium dihydrogen phosphate, sodium phosphate, and ammonium dihydrogen phosphate.
[0017] The present invention provides a sodium-rich polyanion positive electrode material Na z MnTi 1-x-y M x A y (PO4)3 and its preparation method have the following beneficial effects: First, the rate performance is excellent. Due to the inherent sodium vacancies in the material, by reducing the high-valence Ti content in the synthesis process, the alkali metals, alkaline earth metals, and other metal elements with lower valence states work together, without changing the valence states of other transition metal ions, according to the principle of charge conservation, the corresponding sodium content is added, thereby filling the sodium vacancies in the material and increasing the sodium content in the material. The sodium-rich material electrode has better rate performance (at a rate of 10 C, there is still a capacity of about 150mAh / g, which is better than most sodium ion battery positive electrode materials). Due to the increase in the sodium content in the unit cell, without changing the space group (R-3c) of the material, the unit cell volume of the material becomes larger, the diffusion channel of the sodium ions becomes wider, the diffusion rate of the sodium ions becomes faster, and the material has better rate performance.
[0018] Second, the cycle stability is good. The sodium-rich material electrode has better cycle stability (at 1 C rate, the capacity retention rate of 100 cycles is more than 95%). During the operation of the battery, the sodium in the material is not only repeatedly embedded and de-embedded in the material, but also plays the role of supporting the material. The sodium content in the sodium-rich material is higher, which helps to support the structure of the material and weakens the structural changes of the material during the process of sodium embedding and de-embedding.
[0019] Third, the capacity is high. In the whole battery, the active sodium is provided by the positive electrode, and during the operation of the battery, the formation of the solid electrolyte layer (SEI) on the negative electrode side consumes the active sodium. Therefore, the more sodium content in the positive electrode material, the more conducive it is to the capacity of the material. The more active sodium sites in the sodium-rich material, the more total amount of sodium that can participate in the deintercalation reaction, and the gram capacity of the material increases. In addition, it can also make up for the active sodium consumed in the negative electrode, improving the capacity of the material in the whole battery.
[0020] Fourth, the degree of pure phase is high. The chelating groups in the organic acid and the hydrogen ions generated by ionization in the solution can control the pH value of the solution and chelate the transition metal ions at the same time, ensuring that during the mixing process of the first precursor solution and the second precursor solution, the transition metal ions will not combine with the phosphate radicals to produce precipitation and cause phase separation, thereby achieving atomic-level mixing of various elements and ensuring that pure phase materials are finally prepared. In addition, the organic acid decomposes during the high-temperature solid-phase reaction to produce a carbon layer covering the surface of the active material particles, further improving the electronic conductivity of the material interface and improving the electrochemical performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 For Example 1 synthetic material Na 3.55 MnTi 0.75 Fe 0.2 Na 0.05 XRD structure of (PO4)3; Figure 2 Example 2 Synthetic Material Na 3.35 MnTi 0.85 Fe 0.1 K 0.05 XRD structure of (PO4)3; Figure 3 For Example 3 synthetic material Na 3.2 MnTi 0.9 Cr 0.05 Na 0.05 XRD structure of (PO4)3; Figure 4 For Example 4 synthetic material Na 3.5 MnTi 0.8 Ni 0.1 Na 0.1XRD structure of (PO4)3; Figure 5 This is the XRD structure diagram of the synthetic material Na3MnTi(PO4)3 of Comparative Example 1; Figure 6 The charge and discharge curves of Example 1 and Comparative 1 materials are shown; Figure 7 The charge and discharge curves of Example 2 and Comparative 1 materials are shown; Figure 8 The charge and discharge curves of Example 3 and Comparative 1 materials are shown; Fig. 9 The charge and discharge curves of Example 4 and Comparative 1 materials are shown in FIG. DETAILED DESCRIPTION
[0022] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.
[0023] The present invention discloses a sodium-rich polyanion positive electrode material, the general structural formula of which is Na z MnTi -x- y M x A y (PO4)3; the value range of z is 3<z≤4, the value range of x is 0<x<1, and the value range of y is 0<y≤0.33; M is one or more of the metal elements Al, V, Cr, Mn, Fe, Ni, Cu, and Zn, and A is one or more of the alkali metal or alkaline earth metal elements Li, Na, K, Mg, and Ca.
[0024] Another aspect of the present invention is to protect the preparation method of the above-mentioned sodium-rich polyanion positive electrode material, comprising the following steps: S1. Preparation of a first precursor solution: dissolving a manganese source, a titanium source, a metal M source, an alkali metal or alkaline earth metal A source, a carbon source and a first acid solution to form a first precursor solution, and adding a second acid solution organic acid to control the pH value of the first precursor solution to be in the range of 1 to 3; S2, preparation of a second precursor solution: mixing and dissolving a sodium source and a phosphorus source to form a second precursor solution; S3, preparation of a third precursor solution: uniformly mixing the second precursor solution with the first precursor solution to obtain a third precursor mixed system; S4, preparation of precursor powder: drying the third precursor mixture system to obtain precursor powder; S5. Sintering preparation of sodium-rich polyanion positive electrode material: The precursor powder is calcined at high temperature and then cooled to obtain the sodium-rich polyanion positive electrode material.
[0025] Furthermore, in step S1, the feed ratio of the manganese source, the titanium source, the metal M source, and the A source is prepared according to a metal ion molar ratio of 1: (0.01-0.99): (0.01-0.99): (0.01-0.33).
[0026] Furthermore, in step S2, the feeding ratio of the sodium source and the phosphorus source is prepared according to a sodium-phosphorus molar ratio of 1 to 1.5.
[0027] Furthermore, in step S3, the first precursor solution and the second precursor solution are fed in a ratio according to a molar ratio of phosphorus to manganese of 0.5-5.
[0028] Furthermore, in step S4, the drying method is flash drying and / or spray drying, and the drying temperature ranges from 110 to 250°C.
[0029] Furthermore, in step S5, the high temperature calcination conditions are: sintering temperature is 550-750°C, holding time is 5-15h, and calcination atmosphere is an inert atmosphere, which is argon and / or nitrogen.
[0030] Furthermore, in steps S1 and S2, the manganese source is one or more of manganese sulfate, manganese acetate, manganese chloride, and manganese nitrate; the titanium source is one or more of titanium tetrachloride, tetrabutyl titanate, isopropyl titanate, titanium isopropoxide, titanium sulfate, titanyl sulfate, bis(trifluoromethanesulfonate) titanocene, and dihydroxybis(ammonium lactate) titanium; the metal M source is one or more of the sulfate, chloride, nitrate, and oxalate of M; the alkali metal or alkaline earth metal A source is one or more of the sulfate, chloride, nitrate, carbonate, and oxalate of A.
[0031] Furthermore, in step S1, the carbon source is one or more of glucose, citric acid, sucrose, maltose, water-soluble starch, and lactose, and the added amount of the carbon source is 0.5~10wt%; the first acid solution is one or more of nitric acid, acetic acid, formic acid, oxalic acid, ascorbic acid, tartaric acid, and citric acid.
[0032] Furthermore, in step S2, the sodium source is one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium formate, sodium acetate, sodium sulfate, sodium nitrate, and trisodium citrate; the phosphorus source is one or more of phosphoric acid, sodium monohydrogen phosphate, sodium dihydrogen phosphate, sodium phosphate, and ammonium dihydrogen phosphate.
[0033] Example 1 This embodiment relates to a sodium-rich polyanion positive electrode material Na 3.55 MnTi 0.75 Fe 0.2 Na 0.05 (PO4)3, the preparation method thereof comprises the following steps: S1. Preparation of a first precursor solution: manganese acetate, titanium source dihydroxybis(ammonium lactate) titanium, ferric nitrate, and sodium acetate are added in a ratio of 1:0.75:0.2:0.05 as a metal ion molar ratio to prepare an aqueous solution, and citric acid (which serves as both a carbon source and an acid) is added to dissolve and adjust the pH to ≈ 1.3 to obtain a first precursor solution; S2, preparation of a second precursor solution: sodium acetate and ammonium dihydrogen phosphate are prepared according to a sodium-phosphorus molar ratio of 1.18, and water is added to dissolve to obtain a second precursor solution; S3. Preparation of the third precursor mixed system: slowly drop the second precursor solution into the first precursor solution and mix them evenly. The feed ratio is set according to the molar ratio of phosphorus to manganese contained therein of 3.
[0034] S4. Preparation of precursor powder: The third precursor mixture system obtained in step S3 is granulated by spray drying at a drying temperature of 230° C. to obtain dry precursor powder.
[0035] S5. Sintering preparation of sodium-rich polyanion positive electrode material: calcine the precursor powder obtained in step S4 to 700° C. at high temperature, keep the temperature for 10 hours, and cool naturally to obtain the material.
[0036] In a dry environment, sodium-rich polyanion cathode material, AB, and PVDF were mixed and slurried in a mass ratio of 9.2:0.4:0.4. The black slurry was then coated on aluminum foil using a 150µm four-sided preparation device, and the film was dried in a vacuum oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6mm using a punching machine, with metallic sodium as the counter electrode, 1mol / L NaClO4EC+DEC (1:1vol%)+5%FEC as the electrolyte, and a PP / PE / PP three-layer diaphragm as the separator, and assembled into a CR2016 button cell in a glove box.
[0037] Example 2 This embodiment relates to a sodium-rich polyanion positive electrode material Na 3.35 MnTi 0.85 Fe 0.1 K 0.05 (PO4)3, the preparation method thereof comprises the following steps: S1. Preparation of a first precursor solution: manganese nitrate, dihydroxydi(ammonium lactate)titanium, ferric nitrate, and potassium oxalate are fed in a ratio of 1:0.85:0.1:0.05 as a metal ion molar ratio to prepare an aqueous solution, citric acid (which serves as both a carbon source and an acid) is added to dissolve and adjust to pH≈2, and glucose is added at a mass percentage of 0.5% to dissolve to obtain a first precursor solution; S2. Preparation of a second precursor solution: sodium oxalate and ammonium dihydrogen phosphate are prepared according to a sodium-phosphorus molar ratio of 1.12, and water is added to dissolve to obtain a second precursor solution; S3. Preparation of the third precursor mixed system: slowly drop the second precursor solution into the first precursor solution and mix them evenly. The feed ratio is set according to the molar ratio of phosphorus to manganese of 1.2.
[0038] S4. Preparation of precursor powder: The third precursor mixture system obtained in step S3 is granulated by spray drying at a drying temperature of 170° C. to obtain dry precursor powder.
[0039] S5. Sintering preparation of sodium-rich polyanion positive electrode material: calcining the precursor powder obtained in step S4 to 600° C. at high temperature, keeping the temperature for 15 hours and cooling naturally to obtain the material.
[0040] In a dry environment, sodium-rich polyanion cathode material, AB, and PVDF were mixed and slurried in a mass ratio of 9.2:0.4:0.4. The black slurry was then coated on aluminum foil using a 150µm four-sided preparation device, and the film was dried in a vacuum oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6mm using a punching machine, with metallic sodium as the counter electrode, 1mol / L NaClO4EC+DEC (1:1vol%)+5%FEC as the electrolyte, and a PP / PE / PP three-layer diaphragm as the separator, and assembled into a CR2016 button cell in a glove box.
[0041] Example 3 This embodiment relates to a sodium-rich polyanion positive electrode material Na 3.2 MnTi 0.9 Cr 0.05 Na 0.05 (PO4)3, the preparation method thereof comprises the following steps: S1. Preparation of a first precursor solution: manganese acetate, dihydroxydi(ammonium lactate)titanium, chromium nitrate, and sodium oxalate are added in a ratio of 1:0.9:0.05:0.05 as a metal ion molar ratio to prepare an aqueous solution, and citric acid (which serves as both a carbon source and an acid) is added to dissolve and adjust the pH to ≈ 1.3 to obtain a first precursor solution; S2. Preparation of a second precursor solution: sodium oxalate and ammonium dihydrogen phosphate are prepared according to a sodium-phosphorus molar ratio of 1.07, and water is added to dissolve to obtain a second precursor solution; S3. Preparation of the third precursor mixed system: slowly drop the second precursor solution into the first precursor solution and mix them evenly. The feed ratio is 5 according to the molar ratio of phosphorus to manganese contained therein.
[0042] S4. Preparation of precursor powder: The third precursor mixture system obtained in step S3 is granulated by spray drying at a drying temperature of 150° C. to obtain dry precursor powder.
[0043] S5. Sintering preparation of sodium-rich polyanion positive electrode material: The precursor powder obtained in step S4 is calcined at a high temperature to 750° C., kept at this temperature for 7 hours, and then naturally cooled to obtain the material.
[0044] In a dry environment, sodium-rich polyanion cathode material, AB, and PVDF were mixed and slurried in a mass ratio of 9.2:0.4:0.4. The black slurry was then coated on aluminum foil using a 150µm four-sided preparation device, and the film was dried in a vacuum oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6mm using a punching machine, with metallic sodium as the counter electrode, 1mol / L NaClO4EC+DEC (1:1vol%)+5%FEC as the electrolyte, and a PP / PE / PP three-layer diaphragm as the separator, and assembled into a CR2016 button cell in a glove box.
[0045] Example 4 This embodiment relates to a sodium-rich polyanion positive electrode material Na 3.5 MnTi 0.8 Ni 0.1 Na 0.1 (PO4)3, the preparation method thereof comprises the following steps: S1. Preparation of the first precursor solution: manganese acetate, titanium source dihydroxybis(ammonium lactate) titanium, nickel nitrate, and sodium nitrate are added in a ratio of 1:0.8:0.1:0.1 as a metal ion molar ratio to prepare an aqueous solution, citric acid (which serves as both a carbon source and an acid) and nitric acid are added to dissolve and adjust to pH≈2.7, sucrose is added at a mass percentage of 7%, and dissolved to obtain a first precursor solution; S2. Preparation of a second precursor solution: sodium nitrate and ammonium dihydrogen phosphate are prepared according to a sodium-phosphorus molar ratio of 1.17, and water is added to dissolve to obtain a second precursor solution; S3. Preparation of the third precursor mixed system: slowly drop the second precursor solution into the first precursor solution and mix them evenly. The feed ratio is set according to the molar ratio of phosphorus to manganese contained therein of 3.
[0046] S4. Preparation of precursor powder: The third precursor mixture system obtained in step S3 is granulated by spray drying at a drying temperature of 120° C. to obtain dry precursor powder.
[0047] S5. Sintering preparation of sodium-rich polyanion positive electrode material: calcine the precursor powder obtained in step S4 to 700° C. at high temperature, keep the temperature for 10 hours, and cool naturally to obtain the material.
[0048] In a dry environment, sodium-rich polyanion cathode material, AB, and PVDF were mixed and slurried in a mass ratio of 9.2:0.4:0.4. The black slurry was then coated on aluminum foil using a 150µm four-sided preparation device, and the film was dried in a vacuum oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6mm using a punching machine, with metallic sodium as the counter electrode, 1mol / L NaClO4EC+DEC (1:1vol%)+5%FEC as the electrolyte, and a PP / PE / PP three-layer diaphragm as the separator, and assembled into a CR2016 button cell in a glove box.
[0049] Comparative Example 1 This embodiment relates to an unmodified non-sodium-rich polyanion positive electrode material Na3MnTi(PO4)3, and its preparation method comprises the following steps: S1. Preparation of a first precursor solution: manganese acetate and dihydroxybis(ammonium lactate)titanium are fed in a ratio of 1:1 to prepare an aqueous solution, and citric acid (which serves as both a carbon source and an acid) is added to dissolve and adjust the pH to ≈ 1.3 to obtain a first precursor solution; S2, preparation of a second precursor solution: sodium acetate and ammonium dihydrogen phosphate are prepared according to a sodium-phosphorus molar ratio of 1, and water is added to dissolve to obtain a second precursor solution; S3. Preparation of the third precursor mixed system: slowly drop the second precursor solution into the first precursor solution and mix them evenly. The feed ratio is set according to the molar ratio of phosphorus to manganese contained therein of 3.
[0050] S4. Preparation of precursor powder: The third precursor mixture system obtained in step S3 is granulated by spray drying at a drying temperature of 230° C. to obtain dry precursor powder.
[0051] S5. Sintering preparation of non-sodium-rich polyanion positive electrode material: calcining the precursor powder obtained in step S4 to 700° C. at high temperature, keeping the temperature for 10 hours and cooling naturally to obtain the material.
[0052] In a dry environment, non-sodium-rich polyanion cathode material, AB, and PVDF were mixed and slurried in a mass ratio of 9.2:0.4:0.4. The black slurry was then coated on aluminum foil using a 150µm four-sided preparation device, and the film was dried in a vacuum oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6mm using a punching machine, with metallic sodium as the counter electrode, 1mol / L NaClO4EC+DEC (1:1vol%)+5%FEC as the electrolyte, and a PP / PE / PP three-layer diaphragm as the separator, and assembled into a CR2016 button cell in a glove box.
[0053] Table 1 Performance test results The XRD patterns of Examples 1 to 5 and Comparative Example 1 are as follows: Figures 1 to 5 As shown, the obtained materials all belong to the R-3c space group. The button cells of Examples 1 to 5 and Comparative Example 1 were subjected to constant current charge and discharge tests under the potential window of 1.5-4.3V. The results are shown in FIG. Figures 6 to 9 As shown in the curve.
[0054] As shown in Table 1, the sodium-rich cathode materials of Examples 1 to 4 have a first-week discharge capacity of 160.5 mAh / g, 164.5 mAh / g, 162.8 mAh / g, and 167.5 mAh / g, respectively, at a current density of 0.1C (1C = 170 mAh / g), all close to their theoretical capacity of 176 mAh / g, and significantly higher than the discharge capacity of 140.2 mAh / g of the non-sodium-rich cathode material of Comparative Example 1. The main reason is that the number of sodium ions in the sodium-rich material structure is significantly increased, providing more active sodium sites in the material, so that the transition metal redox center is fully activated, and the capacity of the material is significantly increased.
[0055] As shown in Table 1, the sodium-rich cathode materials of Examples 1 to 4 have a first-week discharge capacity of 153.1 mAh / g, 150.8 mAh / g, 148.5 mAh / g, and 151.2 mAh / g, respectively, at a current density of 10C (1C = 170 mAh / g), which are significantly higher than the discharge capacity of 109.4 mAh / g of the non-sodium-rich cathode material in Comparative Example 1. This is because the sodium-rich material has a higher sodium content, and some of the sodium that does not participate in the electrochemical process can support the structure of the material, thereby improving the cycle stability of the sodium-rich material. At the same time, the entire unit cell becomes larger, the diffusion channel of the sodium ions becomes wider, the diffusion rate of the sodium ions is accelerated, and the rate performance of the material is also improved.
[0056] Although the structure of Comparative Example 1 still maintains the R-3c space group. However, under the condition of current density 0.1C, the discharge capacity of the non-sodium-rich positive electrode in the first week is only 140.2mAh / g, indicating that the number of sodium ions participating in the reaction in the material structure is small, which indirectly proves that the material has fewer active sodium sites. In addition, compared with the sodium-rich material, the amount of sodium used for the supporting structure is reduced, and the cycle stability and rate performance of the material are reduced. Compared with the capacity retention rate (>90%) after 100 cycles of Examples 1 to 4, that of Comparative Example 1 is only 87%.
[0057] The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.
Claims
1. A sodium-rich polyanion positive electrode material, characterized in that: The general structural formula of the positive electrode material is Na z MnTi 1-x- y M x A y (PO4)3; the value range of x is 0<x<1, the value range of y is 0<y≤0.33, the value range of z is 3<z≤4,; M is one or more of the metal elements Al, V, Cr, Mn, Fe, Ni, Cu, and Zn, and A is one or more of the alkali metal or alkaline earth metal elements Li, Na, K, Mg, and Ca.
2. A method for preparing the sodium-rich polyanion positive electrode material according to claim 1, characterized in that The following steps are involved: S1. Preparation of a first precursor solution: dissolving a manganese source, a titanium source, a metal M source, an alkali metal or alkaline earth metal A source, a carbon source and a first acid solution to form a first precursor solution, and adding a second acid solution organic acid to control the pH value of the first precursor solution to be in the range of 1 to 3; S2, preparation of a second precursor solution: mixing and dissolving a sodium source and a phosphorus source to form a second precursor solution; S3, preparation of a third precursor solution: uniformly mixing the second precursor solution with the first precursor solution to obtain a third precursor mixed system; S4, preparation of precursor powder: drying the third precursor mixture system to obtain precursor powder; S5. Sintering preparation of sodium-rich polyanion positive electrode material: The precursor powder is calcined at high temperature and then cooled to obtain the sodium-rich polyanion positive electrode material.
3. The method for preparing the sodium-rich polyanion positive electrode material according to claim 2, characterized in that: In step S1, the feed ratio of manganese source, titanium source, metal M source and A source is prepared according to the metal ion molar ratio of 1: (0.01-0.99): (0.01-0.99): (0.01-0.33).
4. The method for preparing the sodium-rich polyanion positive electrode material according to claim 2, characterized in that: In step S2, the sodium source and the phosphorus source are prepared according to a sodium-phosphorus molar ratio of 1 to 1.
5.
5. The method for preparing the sodium-rich polyanion positive electrode material according to claim 2, characterized in that: In step S3, the first precursor solution and the second precursor solution are added in a ratio according to a molar ratio of phosphorus to manganese of 0.5-5.
6. The method for preparing the sodium-rich polyanion cathode material according to claim 2, characterized in that: In step S4, the drying method is flash drying and / or spray drying, and the drying temperature ranges from 110 to 250°C.
7. The method for preparing the sodium-rich polyanion positive electrode material according to claim 2, characterized in that: In step S5, the high temperature calcination conditions are: sintering temperature is 550-750°C, holding time is 5-15h, and calcination atmosphere is an inert atmosphere, which is argon and / or nitrogen.
8. The sodium-rich polyanion positive electrode material according to claim 2, characterized in that: The manganese source is one or more of manganese sulfate, manganese acetate, manganese chloride, and manganese nitrate; the titanium source is one or more of titanium tetrachloride, tetrabutyl titanate, isopropyl titanate, titanium isopropoxide, titanium sulfate, titanyl sulfate, bis(trifluoromethanesulfonate) titanocene, and dihydroxybis(ammonium lactate) titanium; the metal M source is one or more of sulfate, chloride, nitrate, and oxalate of M; the alkali metal or alkaline earth metal A source is one or more of sulfate, chloride, nitrate, carbonate, and oxalate of A.
9. The sodium-rich polyanion positive electrode material according to claim 2, characterized in that: The carbon source is one or more of glucose, citric acid, sucrose, maltose, water-soluble starch, and lactose, and the added amount of the carbon source is 0.5-10wt%; the first acid solution is one or more of nitric acid, acetic acid, formic acid, oxalic acid, ascorbic acid, tartaric acid, and citric acid.
10. The sodium-rich polyanion positive electrode material according to claim 2, characterized in that: The sodium source is one or more of sodium hydroxide, sodium carbonate, sodium bicarbonate, sodium formate, sodium acetate, sodium sulfate, sodium nitrate, and trisodium citrate; the phosphorus source is one or more of phosphoric acid, sodium monohydrogen phosphate, sodium dihydrogen phosphate, sodium phosphate, and ammonium dihydrogen phosphate.
Citation Information
Patent Citations
Manganese-rich phosphate positive electrode material and preparation method and application thereof
CN113929069A
K-doped polyanion positive electrode material and preparation method thereof
CN117810431A
Sodium battery positive electrode material and preparation method and application thereof
CN119008934A